Zarządzanie wiedzą i strategiczna karta wyników jako czynniki skuteczności zarządzania strategicznego - Kubacka-Góral, Krystyna (Knowledge management and balanced scorecard as factors of effectiveness in strategic management, 2005)
The aim of this paper is to describe the significance and the characterization of Knowledge Management, Balanced Scorecard and Strategic Management. The article presents a few correlations between all of these conceptions allowing for increase the company's competitiveness and effectiveness of implementation of strategy.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1092, s. 422-431